Schooling returns for migrant workers in China: Estimations from the perspective of the institutional environment in a rural setting - Yao, Y.; Chen, G.; Salim, Ruhul; Yu, X. (Elsevier BV * North-Holland, 2017)
We examine schooling returns for migrant workers in China based on the 2009 Rural-Urban Migration in China (RUMiC) survey. Using a novel instrumental variable (IV) set based on the institutional environment unique to rural China, we find the point estimates of returns to lie within the range of 7.8%-10.7% for each additional year of schooling. Whilst our estimates are slightly higher than those reported for this cohort of workers in the literature, they are significantly lower than those enjoyed urban dwellers. Furthermore, we identify a wider gap in schooling returns between male (14.7%) and female (8.5%) migrant workers than the comparable gap for urban dwellers. Our results provide another line of evidence supporting a segmented labor market in urban China and remain robust to different estimators and under various IV restrictions. We suggest that improving the education system in the rural areas and eliminating the gender gap among migrant workers represent the necessary steps for enhancing social harmony in the Chinese society.